TREATMENT OUTCOMES IN PCOS (POLYCYSTIC OVARIAN SYNDROME)-RELATED INFERTILITY - Ibrahim, Aminath Efa; Shareef, Fathimath Ina; Yazdhan, Ahmed; Shabin, Ahmed; Ali, P. Shaik Syed; Ahmad, Md. Parwez (Universal Journal of Pharmaceutical Research, 2024)
Polycystic ovarian syndrome (PCOS) is one of the underdiagnosed endocrine disorders found to be prevalent among females in the reproductive age group. PCOS effects on an average 8-13% of reproductive aged women, globally. This condition is responsible for causing distress physiologically and psychologically paving the way for a poor quality of life. One of the devastating complications of PCOS is infertility. At present, there is no treatment for PCOS but could be managed by alternate options such as lifestyle modification to in-vitro fertilization. The primary objective of this review article is to analyze the outcomes of certain pharmacological treatment options such as clomiphene citrate which is a selective estrogen receptor modulator, Letrozole an aromatase inhibitor, and gonadotropins for PCOS-related infertility. Clomiphene citrate binds to estrogen receptors indirectly increasing the gonadotropins. Studies confirm a 35-40% successful outcome. Letrozole similarly increases gonadotropins by indirectly decreasing estrogen. A notable increase in the successful outcome was observed with both clomiphene citrate and letrozole, with almost near similar results. The pregnancy outcome was approximately 40% with clomiphene citrate, while letrozole showed 50%. Notably, more side effects were observed in the administration of clomiphene citrate compared to letrozole. Human menopausal gonadotropin (hMG) and recombinant follicle-stimulating hormone (FSHr), that are gonadotropins, were used as they are directly responsible for the maturation of follicles and ovulation itself. The use of gonadotropins increased the pregnancy rate outcome to 20 -30 %, albeit with the risk of multiple births. Furthermore, we have discussed why letrozole and clomiphene citrate are used as the primary therapy compared to gonadotropins. Peer Review History: Received 22 May 2024; Reviewed 14 July 2024; Accepted 23 August; Available online 15 September 2024 Academic Editor: Dr. Rola Jadallah , Arab American University, Palestine, rola@aauj.edu Reviewers: Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com Dr. Ogbonna B. Onyebuchi, Nnamdi Azikiwe University, Awka, Nigeria, summitpharm@yahoo.com